2022
DOI: 10.1007/s10459-022-10146-2
|View full text |Cite
|
Sign up to set email alerts
|

Professional identity formation: linking meaning to well-being

Abstract: Trainee distress and burnout continue to be serious concerns for educational programs in medicine, prompting the implementation of numerous interventions. Although an expansive body of literature suggests that the experience of meaning at work is critical to professional wellbeing, relatively little attention has been paid to how this might be leveraged in the educational milieu. We propose that professional identity formation (PIF), the process by which trainees come to not only attain competence, but additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 112 publications
0
17
0
Order By: Relevance
“…This study also highlights the positive role that the experience of caring for a dying patient can play in professional identity formation, the active, iterative process of forming an authentic and well-integrated physician self. 31 In our study, residents commonly found that by noticing emotions and processing their experience of caring for a dying patient, they often formed personally meaningful conclusions about what it means to be a physician. Others identified the act of processing emotions itself as an integral part of their work as a physician.…”
Section: Discussionmentioning
confidence: 62%
“…This study also highlights the positive role that the experience of caring for a dying patient can play in professional identity formation, the active, iterative process of forming an authentic and well-integrated physician self. 31 In our study, residents commonly found that by noticing emotions and processing their experience of caring for a dying patient, they often formed personally meaningful conclusions about what it means to be a physician. Others identified the act of processing emotions itself as an integral part of their work as a physician.…”
Section: Discussionmentioning
confidence: 62%
“…Medical students actively engage with and assimilate into the clinical and teaching environments through participation in medical communities (involving communication, interaction, and mutual support among healthcare teams, research institutions, and patient groups), the pursuit of shared goals (common practice objectives, career goals, and learning goals), and resource sharing. This process allows them to discover a sense of belonging and accomplishment, facilitating the transition from basic learning and work cognition to professional identity [ 8 , 9 ]. The Personality Ring Theory (RToP) also asserts that community participation and interpersonal interaction play crucial roles in promoting the formation of professional identity [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Professional identity formation has become the focus of a diverse range of fields, including medical education [ 26 ]. Among health care professionals, studies have shown that the development of a shared core value set can have substantial benefits, including improving the well-being and resilience of physicians [ 27 ]. Professional identity’s influence in other areas is less well documented, but some benefits may be appreciable across a range of disciplines.…”
Section: Discussionmentioning
confidence: 99%